Effect of Herbal Face Pack on Acne Vulgaris among Young Adult Females – A Randomized Controlled Trial - Sanjita, Konsam; D R, Lakshmeesha, Prajna; Dinachandra, Konsam; Shetty, Vanitha (Indian Journal of Integrative Medicine, 2025)
Background & Objectives: Acne vulgaris (AV) is a chronic inflammatory condition affecting the pilosebaceous unit, which results in scarring and considerable psychological effects, thereby diminishing the quality of life (QoL). Factors such as Propionibacterium acnes, increased sebum production, altered keratinization, and inflammation play a role in the development of acne. Numerous other treatments methods are often expensive and leads to complications. This study seeks to assess the impact of a herbal face pack, composed of turmeric, sandalwood, and neem, on the severity of acne and QoL. Methods: A randomized controlled trial was carried out involving 60 participants, aged between 14 and 25 years diagnosed with AV. Participants were randomly allocated to one of two groups: the study group, which applied a herbal face pack for 20 minutes daily over a period of 30 days and the control group, which received standard medical care. Both groups were advised to refrain from consuming processed foods. Results: The data was analysed using SPSS version 21. Within group comparisons were conducted using t-test and difference-in-difference analysis, revealing a significant reduction in GAGS score in both the study group (p